Alternative payoff mechanisms for choice under risk - James C. Cox; Vjollca Sadiraj; Ulrich Schmidt (Kiel Institute for the World Economy (IfW), 2014)
Most experiments on decision theory ask individual subjects to make more than one decision. The isolation hypothesis is commonly used to justify the choice of the random lottery incentive mechanism as the preferred payoff protocol. This research note reports on the main findings on the theoretical and empirical performance of different payoff mechanisms on eliciting individuals' attitudes toward risk. It challenges the conventional view that the random lottery incentive mechanism introduces no biases in inducing risk preferences.
Keywords: 330